Efektivitas Anger Management Training untuk Menurunkan Perilaku Agresi Verbal pada Remaja Pengguna Game Online Mobile Legends di kota Makassar - Wiwin Saputra; Asniar Khumas; Ahmad Ridfah (Indonesian Journal of Islamic Counseling, 2022)
Verbal aggression arises as a result of uncontrolled emotional anger that is faced. The impact of uncontrolled angry emotions will encourage the individual's desire to do negative things. This research aims to determine the effectiveness of anger management training to reduce the tendency of verbal aggression among teenagers who use the online game Mobile Legends in Makassar City. This research uses a Pretest Post-test Control Group Design research design. The participants in this research were 20 male teenagers who had a tendency towards verbal aggression who were divided into two groups, namely 10 participants in the control group and 10 participants in the experimental group. The data analysis technique uses the Mann-Whitney and Wilcoxon signed rank test. The results of the research show that anger management training is effective on the tendency of verbal aggression in teenagers who use the online mobile legends game in Makassar City (W= 6,000, ρ=0.001) with an effect of -0.880 and is included in the large category. The pre-test results of the experimental group (M = 6,800, SD = 2,440) were greater than the post-test average of the experimental group (M = 3,500, SD = 1,080); and (W = 45,000, ρ=0.008), the control group's pre-test score (M = 6,000, SD = 1.054) was smaller than the control group's post-test mean (M = 6,100, SD = 1.792). Anger management training is used to reduce verbal aggression among adolescent online game players.